Heparin Binding Assay of von Willebrand Factor (vWF) in Plasma Milieu – Evidence of the Importance of the Multimerization Degree of vWF - de Romeuf, Christophe; Mazurier, Claudine (Thrombosis and Haemostasis, 1993)
We developed a simple and fast method for studying the heparin binding of von Willebrand factor (vWF) in the plasma milieu. Using plasma from patients with von Willebrand disease (vWD) subtype II, we found that the heparin binding was impaired when compared with a normal plasma control. Further experiments performed with purified vWF of various multimeric composition, obtained either by gradual reduction or gel filtration, confirmed that heparin binding is dependent on the multimerization of vWF and that high molecular weight (HMW) multimers of vWF are required for normal heparin binding. After reduction of plasma vWF by 1.5 mM DTT, the vWF monomer still binds to heparin but to a lower extent. Under these conditions, no significant differences were obtained between control and patients showing that the heparin binding domain located on the vWF subunit is not altered in the subtypes IIA, IIB and IIC studied.